2023
DOI: 10.3390/jcm12206646
|View full text |Cite
|
Sign up to set email alerts
|

Syringomyelia Is Associated with a Reduction in Spinal Canal Compliance, Venous Outflow Dilatation and Glymphatic Fluid Obstruction

Grant Alexander Bateman,
Alexander Robert Bateman

Abstract: The cause of the cystic dilatation of the cord found in syringomyelia has been a source of conjecture for a considerable time. Recent studies have shown that there is a reduction in craniospinal compliance in both childhood hydrocephalus and multiple sclerosis which leads to venous outflow dilatation. Both diseases are associated with glymphatic outflow obstruction. Venous dilatation will narrow the perivenous glymphatic outflow pathway and lead to an increase in glymphatic outflow resistance. Syringomyelia ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The current authors have suggested that there is likely to be obstruction of the glymphatic system, due to dilatation of the venous outflow. This dilatation has been shown to occur in childhood hydrocephalus, multiple sclerosis and syringomyelia and obstruction occurs because of a shared outflow geometry 14,15 (see Fig. 1B).…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…The current authors have suggested that there is likely to be obstruction of the glymphatic system, due to dilatation of the venous outflow. This dilatation has been shown to occur in childhood hydrocephalus, multiple sclerosis and syringomyelia and obstruction occurs because of a shared outflow geometry 14,15 (see Fig. 1B).…”
mentioning
confidence: 85%
“…In childhood hydrocephalus, the bridging cortical veins are found to be 22% larger than in controls 28 . Dilatation of the outflow veins of the brain has been suggested to obstruct the glympathic pathway because they share a common outflow geometry 15 (see Fig. 1B).…”
Section: Similarities Between Sans and Hydrocephalusmentioning
confidence: 99%
See 2 more Smart Citations
“…The glymphatic fluid flow in the brain is hypothesised to occur by CSF inflow into the arterial perivascular spaces and outflow via the perivenous spaces [70]. Dilatation of the veins would be expected to narrow the venous perivascular spaces and impede the glymphatic outflow [71]. MRI imaging techniques confirm there is glymphatic obstruction in NPH and there is a significant improvement in glymphatic flow following shunt insertion [72].…”
Section: Hydrocephalus (Fig 2e) Appears To Be An Amalgamation Of the ...mentioning
confidence: 99%